Improving Strategies of the Private Sector Participation in Telecom Sector in Egypt - Khaled Fayez Bazeed (Newinera Publisher, 2021)
The research aims to identify Improving strategies of the private sector participation of Telecom sector in Egypt and the research has found the high level the government’s role in improving private sector participation strategies in Egypt and The Medium level of Strategies of the private sector participation in Egypt and there is a statistically significant impact the government’s role in improving private sector participation strategies on Strategies of the private sector participation in Egypt in Telecom sector in Egypt and the more it increased level the government’s role in improving private sector participation strategies 1% is Strategies of the private sector participation in Egypt in Telecom sector in Egypt has increased 0.982%. The study has recommended the need to work to increase the level of awareness and culture of the community about the importance of the participation of the private sector in all economic and production fields, the government works to provide all financial, human, technological and legal capabilities and needs in order to encourage the private sector to participate in all economic and productive sectors in Egypt, work to encourage the private sector to abide by the responsibility towards the society in which it works and to provide all possibilities to improve the standard of living for its employees, working to provide legislation and laws that allow the private sector to participate positively and effectively in all areas, which contributes to achieving the required development goals.